Case Study Of Prestsar Group - Low, Say Giat (2006)
This case study is concerned with the marketing strategies and business strategies of one of the leading steel service centre, Prestar Group, in Malaysia. In short, this paper will integrate and apply the strategic management and marketing management theories and practices towards solving company issues and problems.